Evaluation of the Relation Between Impacted Mandibular Third Molar Classification and Inferior Alveolar Canal - Ertem, Sinan Yasin; Anlar, Halil (UI Scholars Hub, 2020)
Objective: The development, eruption, and proximity of mandibular third molars with the inferior alveolar canal are highly variable. The classification of mandibular third molars and their relationship with the inferior alveolar canal were discussed. Methods: A total of 1,024 orthopantomograms (OPGs) from 422 male patients and 602 female patients were examined. The position of the mandibular third molars and their proximity to the inferior alveolar canal were evaluated. Results: Mandibular third molars were observed in 652 (63.67%) of the 1,024 OPGs. According to the Winter’s classification, the most common position of third molars was the vertical position (72.38%). Under the Pell and Gregory classification, the most common relationship with ramus was Class l (74.40%), and the most common impaction depth was Level A (73.94%). As for the relationship between the mandibular third molars and the inferior alveolar canal, the most common positions were horizontal (35.44%), Class II (35.20%), and Level C (43.31%). Among the mandibular third molars adjacent to the inferior alveolar canal, the most common positions were horizontal (39.24%), Class III (57.83%), and Level C (35.43%). Conclusion: The most common classifications for the mandibular third molars were vertical, Class I, and Level A. Exactly 33.67% of the mandibular third molars were related or adjacent to the inferior alveolar canal, and their most common positions were horizontal, Class III, and Level C.